The impact of knowledge management on organizational performance in today's economy - Saqib, Muhammad; Mohammed Din, Zulkifli; Baluch, Nazim Hussain (South East Asia Journal of Business Economics and Law, 2017)
Knowledge is the currency of today’s economy and the crux of knowledge management, which in turn the lifeline of modern-day organizations.It has been used since 1990s as a tool to achieve sustainable competitive advantages and greater performance, and now, it is becoming an essential asset to sustain organizational competitive advantages and a vehicle for continuous progress and innovation. It is every organization’s objective to be able to grow and progress whether it is an SME or a large enterprise so to ensure that there is return on investment of the shareholders and this objective can be met through sustainable superior organizational performance. There are many determinants that may influence organizational performance operating in the current economy but one that is being increasingly recognized as vital is knowledge management. This article has two objectives: The first is to provide an overview of knowledge management and highlight the importance of this field of practice, and the second is to provide few case studies of the successful implementation of knowledge management from different industries. Thus, we will further explore the notion that knowledge management positively impacts organizational performance through the analysis of a number of case studies where knowledge management is being practiced. We will start by highlighting the general interpretation of organizations, the current economy within which they are operating, the concept of knowledge management and how it may be used within organizations. This will be followed by an analysis of cases of knowledge management being practiced and the impact it has had on the overall performances, and finally present our argument that suggest knowledge management positively impacts organizational performances.